2008
DOI: 10.1001/archsurg.143.6.575
|View full text |Cite
|
Sign up to set email alerts
|

Modified Radical Mastectomy With Axillary Dissection Using the Electrothermal Bipolar Vessel Sealing System

Abstract: The use of the electrothermal bipolar vessel sealing system is feasible, safe, and effective in modified radical mastectomy with axillary dissection in terms of lymph vessel sealing, hemostasis, and perioperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 27 publications
0
36
0
1
Order By: Relevance
“…[3][4][5][6] Therefore, many studies have been performed by using various electrosurgical device to reduce this complications. [17][18][19][20][21] In addition, it is demonstrated that the use of EC increases the incidence of seroma formation. 22 Therefore, the use of different energy sources has become widespread to prevent ischemia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] Therefore, many studies have been performed by using various electrosurgical device to reduce this complications. [17][18][19][20][21] In addition, it is demonstrated that the use of EC increases the incidence of seroma formation. 22 Therefore, the use of different energy sources has become widespread to prevent ischemia.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have been shown the efficacy of bipolar devices such as ultrasonic scissors and electrothermal bipolar vessel sealing systems to reduce the seroma formation. 19,21 However, PB is a monopolar energy source, and coagulates the vessels with the heat generated by radiofrequency. The PB's working principle is similar to electrocautery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha demostrado que el volumen de débito del drenaje axilar y la aparición de seroma, si el drenaje es retirado de forma precoz, son independientes de la técnica quirúrgica realizada, de los instrumentos de disección y sellado utilizados [5][6][7][8] o de la adición de sellantes de fibrina 9 .…”
Section: Factores Asociados a Mayor Débito De Drenaje Tras Linfadenecunclassified
“…It provides a new alternative for dissection and hemostasis with one instrument, which relies on the principle of bipolar electrocoagulation, and seals blood vessels up to 7 mm in diameter [4]. It has been described with increasing frequency in various procedures (thyroid [5], esophageal [6], lung [7], hepatobiliary [8], gynecological [9], breast [10], etc. ), and the technology holds the promise of reducing surgical time and intraoperative blood loss.…”
Section: Introductionmentioning
confidence: 99%